2010
DOI: 10.3402/ijch.v69i4.17676
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes mellitus among women born in Greenland: measuring the effectiveness of the current screening procedure

Abstract: Objectives. To estimate the prevalence of gestational diabetes mellitus (GDM) among Greenlanders and to evaluate the quality of the current screening procedure for gestational diabetes. Study design. Observational retrospective study of consecutive birth-log data and medical records on pregnant women who had given birth in Nuuk during 2008. Methods. Information about maternal weight, weight gain in pregnancy, height, blood pressure, result of oral glucose tolerance test, family history of diabetes, smoking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…It was stated that plasma calibrated handheld glucometers is acceptable to use for the diagnosis of glucose intolerance in pregnancy in locations where laboratory support is either unavailable or at a site remote to the point of care [20]. The prevalence of WHO 2013 GDM at 6.8% reported in this study is the highest prevalence of GDM reported in Greenland until now [10]. This may be a result of the increasing prevalence of overweight and obesity observed among Greenlandic women within the last 2 decades [21].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It was stated that plasma calibrated handheld glucometers is acceptable to use for the diagnosis of glucose intolerance in pregnancy in locations where laboratory support is either unavailable or at a site remote to the point of care [20]. The prevalence of WHO 2013 GDM at 6.8% reported in this study is the highest prevalence of GDM reported in Greenland until now [10]. This may be a result of the increasing prevalence of overweight and obesity observed among Greenlandic women within the last 2 decades [21].…”
Section: Discussionmentioning
confidence: 88%
“…Globally, the prevalence of GDM has increased within the last 20 years [8,9]. The first study of GDM performed in Greenland reported a very low prevalence of GDM among women from Nuuk who gave birth in 2008 [10]. However, only 54% of eligible women was actually tested with an oral glucose tolerance test (OGTT) for GDM [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral glucose challenge test (OGCT), a tolerance test to 50 grams glucose, and oral glucose tolerance test (OGTT), a tolerance test to 75 or 100 grams glucose, were suggested as screening and diagnostic tests for GDM, respectively (9, 10). The incidence of GDM was reported between 1 to 14% of all pregnancies in various regions of the world (11)(12)(13)(14)(15) and its incidence in Iran was estimated about 4.5% of all pregnancies (16,17), but it has indicated that the rate of GDM is increasing in different countries and it is going to become an important public health problem, mainly among women aged 35-39 years (18)(19)(20)(21). So the current study was done as a preliminary study to compare the current rate of GDM in Urmia city, a northwest province in Iran with previously reported rate.…”
Section: Gestational Diabetes Mellitus In Iranian Womenmentioning
confidence: 98%
“…This may potentially reduce diabetes prevalence among people born after the 1950's. Pedersen et al (3) suggest that the unexpected low prevalence of gestational diabetes found in Greenland -despite a very high prevalence of diabetes in the adult population in Greenland -could be the beginning of a decrease in diabetes prevalence as a consequence of lower rates of low birth weight over the last decades. If the risk of diabetes associated with birth weight has decreased, as the study indicates, this has adverse implications for the future incidence of diabetes.…”
Section: Special Editorialmentioning
confidence: 99%